2015
DOI: 10.1093/jxb/erv169
|View full text |Cite
|
Sign up to set email alerts
|

PacCYP707A2 negatively regulates cherry fruit ripening while PacCYP707A1 mediates drought tolerance

Abstract: Highlight PacCYP707A2 plays a primary role in regulating ABA levels during the onset of cherry fruit ripening, while PacCYP707A1 regulates the ABA content in response to dehydration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 42 publications
2
46
0
Order By: Relevance
“…Moreover, down-regulation of FaNCED1 , which encodes 9- cis -epoxycarotenoid dioxygenase (a rate-limiting enzyme in ABA biosynthesis), and FaBG3 , which encodes β-glucosidase (an enzyme which hydrolyzes ABA glucose esters to release free ABA), led to the delay of fruit ripening and coloration, presumably due to a decrease of free ABA levels in these fruits [12, 14]. These data are supported by additional work performed in sweet cherry, where decreasing the transcriptional level of PacCYP707A2 , which encodes a key enzyme in the oxidative catabolism of ABA, via VIGS (Virus Induced Gene Silencing), led to an increase in the ABA content and promoted the coloration and ripening of fruit [15]. Recent work has demonstrated that ABA is not only important in the ripening of non-climacteric fruits, but also plays an essential role in the ripening of several climacteric fruits, particularly tomato.…”
Section: Introductionmentioning
confidence: 73%
“…Moreover, down-regulation of FaNCED1 , which encodes 9- cis -epoxycarotenoid dioxygenase (a rate-limiting enzyme in ABA biosynthesis), and FaBG3 , which encodes β-glucosidase (an enzyme which hydrolyzes ABA glucose esters to release free ABA), led to the delay of fruit ripening and coloration, presumably due to a decrease of free ABA levels in these fruits [12, 14]. These data are supported by additional work performed in sweet cherry, where decreasing the transcriptional level of PacCYP707A2 , which encodes a key enzyme in the oxidative catabolism of ABA, via VIGS (Virus Induced Gene Silencing), led to an increase in the ABA content and promoted the coloration and ripening of fruit [15]. Recent work has demonstrated that ABA is not only important in the ripening of non-climacteric fruits, but also plays an essential role in the ripening of several climacteric fruits, particularly tomato.…”
Section: Introductionmentioning
confidence: 73%
“…The expression of AAO3 and ABA2 were elevated in dehydration stressed Arabidopsis, which explained that AAO3 and ABA2 participated in plants tolerance to drought stress [45][46][47] . While abscisic acid 8'-hydroxylases (CYP707A1) involved in ABA catabolism, regulated ABA content in Arabidopsis, sweet cherry 48,49 . Besides, ABA biosynthesis in root was also regulated by leaf dehydration to trigger ABA induced responses in roots 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Medina-Puche et al (2014) showed that F. x ananassa plants subjected to drought stress increased endogenous ABA levels as well as the expression of MYB and anthocyanin accumulation in fruit tissues. Finally, Li et al (2015) showed that silencing the 8 0 -hydroxylase (CYP707A2) gene, which encodes a key enzyme in the oxidative catabolism of ABA, further increased anthocyanin accumulation as well as endogenous ABA levels, and stimulated the expression of the transcription factor MYBA, all compared to the control (without silenced CYP707A2). Consequently, Li et al (2015) suggested that anthocyanin synthesis is tightly regulated by endogenous ABA levels.…”
Section: Induction Mechanism Under Drought Stressmentioning
confidence: 99%